Tinjauan Hukum Kebocoran Data Pribadi Konsumen dalam Transaksi Elektronik Berdasarkan Perspektif Pasal 1365 KUHPERDATA - Aufa Aqlani Alparabi; Diky Dikrurahman (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines the legal liability of electronic system providers for the leakage of consumer personal data in electronic transactions based on Article 1365 of the Civil Code and the legal remedies consumers can take to obtain compensation. The study uses a normative juridical method with a statutory and conceptual approach. The results show that personal data leakage can be classified as an unlawful act if it meets the elements of Article 1365 of the Civil Code. Consumers can pursue civil lawsuits, seek protection under the Consumer Protection Law and seek administrative mechanisms to obtain legal protection and compensation for personal data leakage.